BACE inhibitors in clinical development for the treatment of Alzheimer's disease. (2nd November 2018) - Panza, Francesco; Lozupone, Madia; Solfrizzi, Vincenzo; Sardone, Rodolfo; Piccininni, Carla; Dibello, Vittorio; Stallone, Roberta; Giannelli, Gianluigi; Bellomo, Antonello; Greco, Antonio; Daniele, Antonio; Seripa, Davide; et al.
ABSTRACT: Introduction : The amyloid hypothesis of Alzheimer's disease (AD) affirms that brain accumulation of amyloid-β (Aβ) oligomers and soluble aggregates represent the major pathological event of the disease. Several anti-Aβ small organic molecules, monoclonal antibodies and antigens were developed to interfere with Aβ production and clearance, including β–site amyloid precursor protein cleaving enzyme (BACE) inhibitors, blocking the first enzymatic step of Aβ formation. All these approaches, including BACE inhibitors, have failed in large randomized clinical trials (RCTs) in mild-to-moderate AD, but further studies are now being carried out in patients at early AD stages and in asymptomatic subjects at risk of developing AD. Areas covered : The paper provides a comprehensive review of BACE inhibitors for AD treatment, focusing on the most advanced compounds in Phase III RCTs. Expert commentary : BACE inhibitors inhibited robustly, and dose-dependently, Aβ formation in cerebrospinal fluid of AD patients, but without cognitive, clinical, or functional benefit in large RCTs. BACE inhibition may be not sufficient to decrease brain Aβ plaques and aggregates. Indeed, several BACE inhibitors were found to be poorly tolerated and some of them failed also in patients with prodromal AD. This may indicate that blocking the formation of nascent Aβ is not useful in AD.